(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Background: Vagus nerve stimulation (VNS) is a non-pharmacological treatment of refractory epilepsy, which also has an antidepressive effect. The favorable combinations of VNS with specific mechanisms of action of antiseizure medication (ASM) on mood and health related quality of life (HrQol)Objectives: This study aim to explore of psychosocial role for epileptic patient with vagus nerve stimulator implantation. Methodology: Institution-based cross-sectional study design was conducted on 100 epileptic patients using a non-probability sampling technique. Tis study was conducted in two randomly selected hospitals of Baghdad zones from December 18,2023 to January 20, 2024. All epileptic patients on treatment follow up at selected public hospitals of Baghdad City was the source population and the sampled epileptic patients was the study population. The data were collected using the WHO-QOL-SF36 questionnaire. The data were coded, cleaned and entered into SPSS version 26.0. for analysis. Descriptive statistics were expressed in frequency, percentage, mean and standard deviation. Simple linear regression Pearson correlation test was used to find an association between dependent variable and each independent variable.